2020
DOI: 10.3389/fevo.2020.00184
|View full text |Cite
|
Sign up to set email alerts
|

ebony Affects Pigmentation Divergence and Cuticular Hydrocarbons in Drosophila americana and D. novamexicana

Abstract: Drosophila pigmentation has been a fruitful model system for understanding the genetic and developmental mechanisms underlying phenotypic evolution. For example, prior work has shown that divergence of the tan gene contributes to pigmentation differences between two members of the virilis group: Drosophila novamexicana, which has a light yellow body color, and D. americana, which has a dark brown body color. Quantitative trait locus (QTL) mapping and expression analysis has suggested that divergence of the ebo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…However, we found weak and variable expression of Gal4 by the Nanos driver and were unable to obtain robust induction of the miRNA. A recent study found similarly unreliable expression of Cas9 using Nanos in the closely related Drosophila novamexicana ( Lamb et al, 2020 ).…”
Section: Methodsmentioning
confidence: 94%
“…However, we found weak and variable expression of Gal4 by the Nanos driver and were unable to obtain robust induction of the miRNA. A recent study found similarly unreliable expression of Cas9 using Nanos in the closely related Drosophila novamexicana ( Lamb et al, 2020 ).…”
Section: Methodsmentioning
confidence: 94%
“…First, the distribution of both “long” versus “short” CHC phenotypes (shown here and in Lamb et al 2020), and allelic variation CG17821, indicate that the “short” phenotype and the CG17821 truncated allele are derived states that arose within the D. americana group. This shift most likely occurred in western lineages that gave rise to contemporary D. novamexicana .…”
Section: Discussionmentioning
confidence: 88%
“…This association is further supported by additional CHC and sequence data from another D. americana population, originally collected in Anderson, IN (species stock center line 15010-0951.00, henceforth IN D. americana ). Lamb et al 2020 characterized CHC divergence between females from this IN D. americana stock and another D. novamexicana line (species stock center 15010-1031.04). The profile for the D. novamexicana line had no long compounds (>C30), a low abundance of C29 compounds, and presence of multiple short alkenes (<C27), consistent with the “short” CHC profile we observe for our D. novamexicana line.…”
Section: Resultsmentioning
confidence: 99%
“…D. americana has a dark body color with uniformly dark abdominal tergites, whereas D. novamexicana exhibits a light pigmentation along the abdominal midline [51], which is a typical pattern of the subgenus. A recent study used reciprocal hemizygosity testing to demonstrate that the difference in abdominal midline pigmentation intensity between the two species was due to ebony [52]. The authors showed that ebony is required for the development of light pigmentation along the dorsal midline in wild-type D. novamexicana .…”
Section: Discussionmentioning
confidence: 99%